2000
DOI: 10.1007/s004670000416
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DRB1 alleles in Kuwaiti children with idiopathic nephrotic syndrome

Abstract: We have studied the effect of HLA-DRB1 alleles on the clinical presentation of 61 Kuwaiti Arab children with idiopathic nephrotic syndrome. DR7(*0701) was the most prevalent DR allele, found in 41/61 patients (67%) compared with 10/59 healthy controls (17%) (p<0.001). DR3(*0301-0308) allele was the second most common, found in 25% of patients compared with 26% of controls (not significant). There was no significant difference between DRB1*0701(DR7)-positive and DRB1*0701-negative patients in terms of steroid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 9 publications
0
12
3
Order By: Relevance
“…Several studies have reported specific HLA alleles to be risk factors of nephrotic syndrome [12,13,14,15,16,17,18,19,20,21], but the results are inconsistent. Most of these studies demonstrated that patients with steroid-sensitive nephritic syndrome (SSNS) have strong associations with certain HLA alleles, but the associated alleles vary in different populations.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…Several studies have reported specific HLA alleles to be risk factors of nephrotic syndrome [12,13,14,15,16,17,18,19,20,21], but the results are inconsistent. Most of these studies demonstrated that patients with steroid-sensitive nephritic syndrome (SSNS) have strong associations with certain HLA alleles, but the associated alleles vary in different populations.…”
Section: Introductionmentioning
confidence: 85%
“…Hence, data from the Shanghai and Singapore studies analyzing HLA frequencies in their controls are of special interest. From table 6, we can see that HLA-DR7 was found to be more frequent in INS children in both Shanghai (40 vs. 11.23%, p = 0.00025) and Kuwait (43 vs. 13%, p < 0.001) [12, 16], while HLA-A*11, rather than the HLA-DR or -DQ alleles, was more frequent in Singaporean patients [17]. However, the frequency of HLA-DR7 was low in both patient and control groups in our study (6.8 and 2.3%, respectively, table 1), which indicated the difference in genetic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been studies from different parts of the world regarding the HLA class II DR and DQ associations with steroid sensitive nephrotic syndrome in children [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Most of these studies are small and have tested only limited alleles and yielded different associations.…”
Section: Introductionmentioning
confidence: 99%